2016
DOI: 10.1136/neurintsurg-2016-012308
|View full text |Cite
|
Sign up to set email alerts
|

Novel methodology to replicate clot analogs with diverse composition in acute ischemic stroke

Abstract: Seven different clot types were developed to replicate common AIS thrombi. These clot analogs may be beneficial for the preclinical evaluation of endovascular therapies, and may be applied to interventional technique training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 29 publications
4
87
0
Order By: Relevance
“…The resistant fibrin rich clot analogues were produced from ovine blood based on the methodology described by Duffy et al 7. Briefly, ovine blood was anticoagulated using sodium citrate solution immediately after collection.…”
Section: Methodsmentioning
confidence: 99%
“…The resistant fibrin rich clot analogues were produced from ovine blood based on the methodology described by Duffy et al 7. Briefly, ovine blood was anticoagulated using sodium citrate solution immediately after collection.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies analyzing clots retrieved from patients have shown that the ratio of fibrin to RBC content can vary from 100% fibrin to almost 80% RBCs 12–14. In our laboratory, we have created a variety of blood clots of different compositions (from 0% to 80% RBC content) based on strict protocols, previously described by our group 15. Some mechanical characterization of clots has been investigated in the past, including tensile, compressive, and rheological properties 16 17.…”
Section: Introductionmentioning
confidence: 99%
“…This is supported by studies that compared the occurrence of the HVS with histological analyses of thrombus formations, proving that thrombus density in CT is proportional to the RBC content and inversely proportional to its fibrin content [14][15][16]. It was also shown that thrombus compositions are associated with its origin and result from the duration of the occlusion [17,18]. Most in-or ex vivo CT studies investigated thrombus composition and the relation to characteristics within unenhanced CT scans (NECT) [10,11,15,19,20].…”
Section: Introductionmentioning
confidence: 74%